Bromfenac in ophthalmic practice - M.L. Maximov; A.A. Zveginceva; I.D. Kanner; N.M. Lapkin (РМЖ "Клиническая офтальмология")
M.L. Maksimov1,2,3, A.A. Zvegintseva1,4, I.D. Kanner5, N.M. Lapkin6 1Kazan State Medical Academy — Branch of the Russian Medical Academy of Continuous Professional Education, Kazan, Russian Federation 2Russian Medical Academy of Continuous Professional Education, Moscow,   Russian Federation 3Pirogov Russian National Research Medical University, Moscow, Russian Federation 4Republican Clinical Hospital of the Ministry of Health of the Republic of Tatarstan,   Kazan, Russian Federation 5Lomonosov Moscow State University, Moscow, Russian Federation 6Yaroslavl State Medical University, Yaroslavl, Russian Federation Non-steroidal anti-inflammatory drugs (NSAIDs) are essential for the treatment of ocular disorders. While corticosteroids are the gold standard for inflammatory ocular diseases, comparative studies on the efficacy of NSAIDs and corticosteroids have demonstrated no significant differences in outcomes. Given the chemical structure of NSAIDs, it should be noted that salicylates, phenamates, and pyrazoline derivatives are either toxic or unstable. Solubilizers and preservatives also account for toxicity. Bromfenac-based medications are characterized by high safety and contain minimum benzalkonium chloride. This paper reviews advantages of a modern topical NSAID, bromfenac, for ocular use. This medication is more effective than diclofenac (by 3.7 times), amfenac (by 6.5 times), and ketorolac (by 18 times) in terms of inhibiting COG-2. Furthermore, the regimen of use (twice daily), no discomfort, and excellent safety profile with minimal adverse effects improve treatment adheren ce. In addition, Bromfenac, a topical anti-inflammatory agent, improves patients’ satisfaction with surgical outcomes since patients achieve maximum possible visual acuity as early as possible. Keywords: non-steroidal anti-inflammatory drugs, NSAIDs, bromfenac, arachidonic acid, inflammation, corticosteroids, eye surgery, cataract, cystoid macular edema. For citation: Maksimov M.L., Zvegintseva A.A., Kanner I.D., Lapkin N.M. Bromfenac in ophthalmic practice. Russian Journal of Clinical Ophthalmology. 2021;21(4):241–248 (in Russ.). DOI: 10.32364/2311-7729-2021-21-4-241-248.